Features of ankylosing spondylitis at different stages in men and women - I. A. Cherentsova; E. N. Otteva (Современная ревматология, 2019)
The incidence of ankylosing spondylitis (AS) has recently increased with a substantial rise in the proportion of female patients, making this investigation relevant.Objective: to investigate the clinical and laboratory parameters of inflammatory activity and functional status in male and female patients with AS at different stages of the disease.Patients and methods. Examinations were performed in 119 patients (82 men and 37 women) (mean age, 36.4±0.9 years) with AS and 34 patients (24 men and 10 women) (mean age 27.0±1.6 years) with non-radiographic axial spondyloarthritis (nr-axSpA). The investigators used the 1984 modified New York criteria to confirm AS diagnosis and the 2009 ASAS classification criteria for axial spondyloarthritis. They also determined AS activity by the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and functional status by the Bath Ankylosing Spondylitis Functional Index (BASFI) and the Bath Ankylosing Spondylitis Metrology Index (BASMI). For the calculation of enthesites, the validated index Maastricht Ankylosing Spondylitis Enthesitis Score (MASES) was used; pain intensity in the last week was estimated using a visual analogue scale (VAS). Laboratory examination included the determination of ESR and HLA-B27 antigen. All the patients underwent a plain film of the pelvic bones; and patients with nr-axSpA had magnetic resonance imaging for sacroiliitis.Results and discussion. In both groups, there was a male preponderance and axial lesions were more common (among the patients with AS, there were 68.9% of the men with sacroiliac joint lesions and 53.7% of those with spinal involvement; among the patients with nr-axSpA, there were 80.0 and 67.6 %, respectively; p>0.05). The HLA-B27 antigen was detected in the majority of patients with AS (86.6% of men and 91.7% of women) and in those with nr-axSpA (91.6 and 80.0%, respectively). Uveitis was more common in women with AS (32.4%), less common in men with AS (17.1%); (p<0.05) and nr-axSpA (8.3%); uveitis was not observed in women with nr-axSpA (p<0.001). The pain according to VAS was more intense in women (48.1±3.4 mm; p<0.01); in the nr-axSpA group, its values were comparable in men and women (p>0.05). The BASDAI and BASFI scores were similar in women at all stages of the disease (p>0.05). The men with nr-axSpA had the best functional status (p<0.01) with the same BASDAI activity (p>0.05) compared with those with AS. The BASMI in patients with AS regardless of gender was higher than in those with nr-axSpA (p<0.01). High BASDAI activity was more frequently detected in women with AS and nr-axSpA than in men (64.9 and 60.0%, respectively; p<0.01). Low activity was not observed in any woman with nr-axSpA. Enthesitis was more common in women in both AS and nr-axSpA (81.0 and 80.0%, respectively; p<0.05).Conclusion. In women, AS and nr-ax-SpA are more severe, starting at their early stage, which is manifested by a higher activity, functional failure, and a higher frequency of extra-axial manifestations.